FROM THE HISTORY OF THE RESEARCH OF HISTORICAL AND ARCHITECTURAL MONUMENTS OF CENTRAL ASIA - Barotjon Ibrahimov (Galaxy International Interdisciplinary Research Journal, 2022)
N in this article. I. The desire to create a wide-ranging scientific biography of veselovsky will give information that will allow new generations to ensure that he does not go unnoticed, to give information about publications that are not always known.